HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIIT PADA PASIEN DIABETUS MELLITUS DI WILAYAH KERJA PUSKESMAS NGUJUNG KABUPATEN MAGETAN - WIDIANTO, ANAS TASIA EKO (STIKes Maharani Malang, 2019)
Introduction: The researcher conducte a preliminary study on various Puskesmas. Puskesmas in Magetan Regency have experience an increase in the number of Diabetus Mellitus patients. One of them is Ngujung Puskesmas. The data that the authors obtained from the Ngujung Puskemas number of patients with medical diagnoses of Diabetus Mellitus is increasing. In 2017 amounting to (0.6%) increase from 2016 which amount to (0.5%). Method: The design in this study uses descriptive analytical types of correlation with the Cross Sectional approach. The population in this study were all patients with Diabetus Mellitus in the working area of the Ngujung Puskesmas in Kabupaten Magetan with a total of 93 people. Samples are obtained using Simple Random Sampling, namely that each population had the same opportunity and opportunity to become a sample. Obtained 48 respondents using the formula. The research instrument was a questionnaire. The statistical test used is Spearman Rank with ? = 0.05.Results and Anaysis: The results of the study showed that most (62.5%) families provided family support for patients with Diabetus Mellitus providing sufficient support. Most (58.3%) compliance with diit in Diabetus Mellitus patients is quite obedient. There is a relationship between family support and adherence of diit in Diabetus Mellitus patients. With p value (0.002) <? (0.05) and correlation coefficient 0.437, which means that the two variables have the strength of the medium relationship.Discussion: There is a Relation between Family Support and Compliance with Diits in Diabetus Mellitus Patients in the Ngujung Puskesmas Working Area in Magetan Regency.